FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPEREMESIS GRAVIDARUM DI RSU MUHAMMADIYAH METRO - Fitri Muriyasari; Ranny Septiani; Herlina Herlina (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2017)
The incidence of hyperemesis gravidarum in RSU Muhammadiyah Metro increase since Year 2014 (5.6%), Year 2015 (11.9%), Year 2016 (12.1%). This study aims to determine the factors associated with the occurence of hyperemesis gravidarum in general hospital MuhammadiyahMetro Year 2016. This research is an analytic correlation research with case control research design. The population in this study were 68 respondents with case samples of 34 respondents and control samples of 34 respondents. Case sampling technique using saturated sample while control sample using simple random sampling. Data collection using checklist. Data analysis used is univariate and bivariate by using Chi Square Test. The results showed that the proportion of hyperemesis gravidarum occurence was 50% of the total sample population, the proportion of maternal age was 36.8%, the proportion of primipara was 33.8%, the proportion of gestational age ≤16 weeks was 39.7%. The result of statistic test showed that there was a correlation between maternal age and hyperemesis gravidarum with p-value 0,002 0,05, there was parity correlation with hyperemesis gravidarum with p-value 0,008 0,05 and there was correlation between gestational age and hyperemesis gravidarum pregnancy with p-value 0.006 0.05. The conclusion of the research obtained is the relationship of maternal age, parity and gestational age with the occurrence of hyperemesis gravidarum at MuhammadiyahMetro Hospital 2016. It is expected for health workers, especially midwives to be able to provide counseling and education to mothers about pregnancy, as well as giving advice to the mother's diet to prevent the occurrence other complications.